FLUID trial: a protocol for a hospital-wide open-label cluster crossover pragmatic comparative effectiveness randomised pilot trial. Issue 8 (23rd August 2018) - McIntyre, Lauralyn; Taljaard, Monica; McArdle, Tracy; Fox-Robichaud, Alison; English, Shane W; Martin, Claudio; Marshall, John; Menon, Kusum; Muscedere, John; Cook, Deborah J; Weijer, Charles; Saginur, Raphael; et al.
Abstract : Introduction: 0.9% saline and Ringer's lactate are the two most common resuscitation crystalloid fluids. 0.9% saline may lead to hyperchloraemic metabolic acidosis and may be associated with impaired kidney function and death. Few large multicentre randomised trials have been conducted to evaluate the effect of these two fluids on clinically important outcomes. Methods: FLUID is a pragmatic pilot cluster randomised crossover trial in which four hospitals will be randomised to normal saline or Ringer's lactate for 14 weeks, then crossover to the alternative fluid for the subsequent 14 weeks after 1 to 3 week transition. With waiver of informed consent, all adult and paediatric patients admitted to participating sites will be included in the FLUID trial except for neonates. Primary feasibility outcome is study fluid protocol adherence (target:≥80%). Secondary feasibility outcomes include time to research ethics board (REB) approval and readiness to trial initiation (≤3 months from REB submission and approval). Primary (composite of death or re-admission to hospital in first 90 days of index hospitalisation) and secondary clinical outcomes for the future large FLUID trial will be described. Protocol adherence will be collected by site at specified time points. All clinical data will be obtained at patient level through provincial health administrative data held at the Institute for Clinical Evaluative Sciences (ICES). Event rates for the primary and secondary outcomes will be described using frequencies and proportions with 95% CIs. Intracluster and interperiod correlation coefficients will be calculated from population-level data available at ICES. Ethics and dissemination: The study protocol has been approved by the Ottawa Health Science Research Ethics Board. The FLUID pilot will determine feasibility, and ICES data across all potential sites in Ontario will allow calculation of sample size parameter estimates to inform the design and implementation of the large trial. Trial registration number: NCT02721485 ; Pre-results.